1983
DOI: 10.1111/j.1476-5381.1983.tb11053.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the electrophysiological actions of phentolamine with those of some other antiarrhythmic drugs on tissues isolated from the rat heart

Abstract: 1Glass microelectrodes were used to record transmembrane electrical activity from cells located just beneath the endocardial surface of segments from the atrial and right ventricular free walls of rat hearts during superfusion and electrical stimulation in vitro at 37°C. 2 Availability of the fast sodium channels for current flow was inferred from the maximum rate of rise of membrane potential during phase 0 of the action potential. 3 Phentolamine mesylate (2 to 20 LM) caused a concentration-dependent block of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 37 publications
5
19
0
Order By: Relevance
“…It should be mentioned that lower concentrations of these agents, such as 9 /IM amosulalol and 16pM phentolamine, which did not exert an appreciable effect on the post-hypoxic recovery of cardiac function and metabolism, appeared to produce little effect on the effective refractory period. Furthermore, phentolamine has been shown to elicit an inhibition of 1 of the action potential in rat ventricular muscle at concentrations ranging from 1 to 20Mm (Northover, 1983). These findings suggest that the beneficial effect of amosulalol and phentolamine observed in the present study is, at least in part, attributable to their membrane stabilizing action, rather than to antagonism of aadrenoceptors.…”
Section: Discussionsupporting
confidence: 51%
“…It should be mentioned that lower concentrations of these agents, such as 9 /IM amosulalol and 16pM phentolamine, which did not exert an appreciable effect on the post-hypoxic recovery of cardiac function and metabolism, appeared to produce little effect on the effective refractory period. Furthermore, phentolamine has been shown to elicit an inhibition of 1 of the action potential in rat ventricular muscle at concentrations ranging from 1 to 20Mm (Northover, 1983). These findings suggest that the beneficial effect of amosulalol and phentolamine observed in the present study is, at least in part, attributable to their membrane stabilizing action, rather than to antagonism of aadrenoceptors.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies showed that the V'max of steady-state action potentials of Purkinje fibres, sinoatrial node or ventricular muscle cells is suppressed by prazosin (Dukes & Vaughan Williams, 1984;Rosen et al, 1984), phentolamine (Ledda & Marchetti, 1971;Northover, 1983), yohimbine (Azuma et al, 1978;Rosen et al, 1984;Briggs & Meier, 1986) and by urapidil, a new a,-adrenoceptor antagonist (Gulch et al, 1986;Kotake et al, 1988). Hasegawa et al (1988) against a2-adrenoceptors (Kameda et al, 1982a,b;Yamanaka et al, 1984) or the low affinity state of x2-adrenoceptors (Yamanaka et al, 1985) and to reverse the a-adrenergic inhibition of insulin release from the pancreatic islet cells (Kameda et al, 1982b).…”
Section: Discussionmentioning
confidence: 99%
“…Northover (1983) considered the antiarrhythmic effects of prazosin, yohimbine, tolazoline, dibenamine and phenoxybenzamine to be produced by interaction with the cell membrane and not by direct inhibition of the a-adrenoceptors. Hasegawa et al (1988) described the suppressive effect of aadrenoceptor antagonists on transient depolarization and triggered activity, and its protective effect against further deterioration of abnormal automatic activity during hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the prolongation of the action potential duration produced by most class III antiarrhythmic drugs decreased at fast rates, i.e., they exhibited a 'reversed usedependence' (Hondeghem & Snyders, 1990). Even when in some studies the inhibitory effects of phentolamine and prazosin on Vmass increased with the frequency of stimulation (Sada, 1978;Northover, 1983;Tohse et al, 1986) the frequency-dependent effects of ax-adrenoceptor antagonists on V,,,lX and APD have not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous electrophysiological studies in different animal species have demonstrated that al-adrenoceptor antagonists inhibited the maximum upstroke velocity (V,,.~) and lengthened the action potential duration (Quadbeck & Reiter, 1975;Sada, 1978;Northover, 1983;Dukes & Vaughan Wilhans, 1984; Rosen et al, 1984;Tohse et at., 1986;Himmel et al, 1991). These results suggested that o1-adrenoceptor antagonists may exhibit class I (Na channel blocking properties) and class III antiarrhythmic properties, respectively, according to the classification of Vaughan Williams (1984).…”
Section: Introductionmentioning
confidence: 99%